Respuesta :

Answer:

Step-by-step explanation:

Finding solutions in a problem like this requires factoring. That means we need to do whatever we have to to isolate the x term. Of course, we have to do it in order of operations but backwards. Begin by adding 2 to both sides to get

[tex](x+4)^2=9[/tex] Now we have to undo the squaring on the left by taking the square root of both sides:

[tex]\sqrt{(x+4)^2}=[/tex] ±[tex]\sqrt{9}[/tex] Taking the square root of a square cancels out both, and of course the square root of 9 is + or - 3:

x + 4 = ±3

The 2 solutions are

x = -4 + 3 which is -1, and x = -4 - 3 which is -7. Choice (3) is the one you want.

ACCESS MORE